Algorithms and Computation 19th International Symposium, ISAAC 2008, Gold Coast, Australia, December 15-17, 2008. Proceedings - Hong, Seok-Hee.; Hong, Seok-Hee.; Nagamochi, Hiroshi.; Nagamochi, Hiroshi.; Fukunaga, Takuro.; Fukunaga, Takuro. (Theoretical Computer Science and General Issues, 2008)
This book constitutes the refereed proceedings of the 19th International Symposium on Algorithms and Computation, ISAAC 2008, held in Gold Coast, Australia in December 2008. The 78 revised full papers together with 3 invited talks presented were carefully reviewed and selected from 229 submissions for inclusion in the book. The papers are organized in topical sections on approximation algorithms, online algorithms, data structure and algorithms, game theory, graph algorithms, fixed parameter tractability, distributed algorithms, database, approximation algorithms, computational biology, computational geometry, complexity, networks, optimization as well as routing.